Fluorous synthesis of 18F radiotracers with the [18F]fluoride ion: nucleophilic fluorination as the detagging process. - Bejot, R; Fowler, T; Carroll, L; Boldon, S; Moore, J; Declerck, J; Gouverneur, V (2009)
Tag team: The flouro-detagging of flourous sulfonates by the [ 18F]fluoride ion was found to be an advantageous strategy for the preparation of various 18F-labeled prosthetic groups and known radiotracers (see picture). Fluorous solid phase extraction (FSPE) was used to separate the excess fluorous precursor from the labeled material, which suggests that traditional purification protocols such as distillation or tedious separation can be avoided. (Chemical Equation Presented). © 2009 Wiley-VCH Verlag GmbH and Co. KGaA.